2004
DOI: 10.1111/j.1537-2995.2004.03426.x
|View full text |Cite
|
Sign up to set email alerts
|

Predonation water ingestion attenuates negative reactions to blood donation

Abstract: Novice blood donors responded positively to predonation water consumption, and they were able to consume 500 mL in less than 5 minutes. Results of the present study suggests that predonation water ingestion may be a simple and cost-effective strategy to enhance the donation experience and possibly increase donor retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 28 publications
1
89
1
1
Order By: Relevance
“…Because vasovagal reactions have been shown to have a negative impact on intention to redonate by adversely affecting attitudes toward donation, interventions that minimize the occurrence of such reactions may positively affect donor return rates. We have demonstrated that simple interventions such as predonation water loading or basic muscle tension techniques have the potential to decrease reaction rates [20][21][22] and hence may lead to more positive attitudes postdonation. Similarly, attending to factors that impact satisfaction with the donation experience (e.g., length of time required to donate, level of privacy) may result in improved attitudes among donors and greater return rates overall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because vasovagal reactions have been shown to have a negative impact on intention to redonate by adversely affecting attitudes toward donation, interventions that minimize the occurrence of such reactions may positively affect donor return rates. We have demonstrated that simple interventions such as predonation water loading or basic muscle tension techniques have the potential to decrease reaction rates [20][21][22] and hence may lead to more positive attitudes postdonation. Similarly, attending to factors that impact satisfaction with the donation experience (e.g., length of time required to donate, level of privacy) may result in improved attitudes among donors and greater return rates overall.…”
Section: Discussionmentioning
confidence: 99%
“…The sample was predominantly white (95%) and nonHispanic (99%), with a mean age of 18.9 years (range, 17-28 years). The mean number of donations was 2.9 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], with the largest proportion of participants reporting one previous donation (34%). Survey responses were collected between September 2005 and March 2006.…”
Section: Participants and Designmentioning
confidence: 99%
“…The BDRI allows to obtain more detailed data from a small group of donations for analysis and to do research with hundreds of donations versus the thousands or tens of thousands of donations that need to be observed for reactions. Such studies can suggest the need for larger observation-based studies, and large observation studies can be more conclusive and relevant [50,51]. …”
Section: Tools To Evaluate Vasovagal Reactionsmentioning
confidence: 99%
“…Therefore as shown in the analysis, adverse reactions of blood donation are a chain of reactions, which starts gradually with a banal vaso-vagal stimulus and then evolves inexorably into syncope, if not adequately treated. [7][8][9][10][11][12] An analysis between age of the donor and adverse reaction was made, 54% of the adverse reactions were seen in the donors of age group 18-28years. 8% of the reactions were seen in 28-38 years age group, 25.7% of reactions were seen in the age group of 38-48 years.28 % of donor reactions were seen in the age group of 48-58 years.…”
Section: Chart 9: Percentage Of Reactions On Y-axis Time Interval Onmentioning
confidence: 99%